Transumbilical laparoscopic appendectomy performed by residents is safe and feasible. Issue 4 (28th June 2016) - Endo, Kazuhiro; Kujirai, Dai; Maeda, Hinako; Ishida, Takashi; Terauchi, Toshiaki; Kimata, Masaru; Shinozaki, Hiroharu; Lefor, Alan Kawarai; Sata, Naohiro
Abstract: Introduction: The aim of this study was to compare the clinical outcomes of single‐incision transumbilical laparoscopy‐assisted appendectomy performed by surgical residents and attending surgeons. Methods: We reviewed the clinical outcomes of 131 transumbilical laparoscopy‐assisted appendectomies performed from January 2011 to June 2014. During the study period, 13 residents and 6 board‐certified attending surgeons performed the procedures. For all operations performed by residents and attending surgeons, we reviewed and compared gender, age, BMI, body temperature, white blood cell count, C‐reactive protein serum level, and the presence of a fecalith or abscess. Clinical outcomes including operative time, estimated blood loss, need for additional ports, conversion to open surgery, intraoperative complications, postoperative complications, and postoperative hospital stay were compared between the two groups. Results: The mean preoperative white blood cell count in the resident‐operated group was significantly higher than in the attending‐operated group (14.0 vs 10.8 ×10 3 /mm 3, P  = 0.007). There were no other significant differences in clinical variables between the two groups. Outcomes show that estimated blood loss was significantly higher (23.4 vs 9.8 mL, P  = 0.031) and operative time tended to be longer (86.0 vs 72.0 min, P  = 0.056) in the resident‐operated group. No other significant differences were observed. Conclusion: Transumbilical laparoscopy‐assisted appendectomy performed by residents is feasible and safe. It is an acceptable as a part of routine surgical training.